TEACHER COMPETENCY AND ONLINE LEARNING MANAGEMENT AS EXPLORATION OF FACTORS AFFECTING STRENGTHENING STUDENT CHARACTER EDUCATION - Badrudin Badrudin; Wahyu Hidayat; Ari Irawan; Angwar Romdoni (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The purpose of this study was to determine the effect of online learning management and teacher personality competence on strengthening students' character education. This research was conducted using a quantitative approach in education management with a descriptive-correlative quantitative method with data collection in the form of questionnaires and interviews. Subjects and research locations are teachers and students at MAN Cimahi City. The results of this study. This study uses the Simultaneous F-Test, which means testing the effect of the X variable together on the Y variable. The basis for decision making, if the value of Sig> 0.05, then Ho is accepted. However, if the value of Sig < 0.05, then Ho is rejected. The Sig value for Regression is 0.042 b. This value is smaller than 0.05; then Ho is rejected. The R Square value of this study was 0.105 or 10.5%. So it can be said that Online Learning Management and Teacher Personality Competence together give an effect of 10.5% the rest (100% - 10.5% = 89.5%) is influenced by other factors.